1992
DOI: 10.1097/00132586-199208000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Cobalamin Inactivation During Nitrous Oxide Anesthesia by Determination of Homocysteine and Folate in Plasma and Urine

Abstract: The effects of nitrous oxideinduced cobalamin inactivation on homocysteine and folate metabolism have been investigated. Plasma levels of cobalamin, folate, homocysteine, and methionine were determined in 40 patients before and after operation under nitrous oxide anesthesia (range of exposure time, 70 to 720 minutes). Twelve patients anesthetized with total intravenous anesthesia served as control subjects (range of exposure time, 115 to 600 minutes). Postoperative plasma levels of folate and homocysteine incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

1994
1994
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…The finding that tHcy levels did not change or slightly increased in patients who were randomly allocated to receive anaesthesia with N 2 O is compatible with the known inhibitory effect of N 2 O on cobalamin which acts as a cofactor of methionine synthase, the key enzyme in the remethylation pathway of homocysteine to methionine [1, 2]. Three previous studies have shown that tHcy increases after surgery [7–9]. In two of these, which were uncontrolled [8] or non‐randomised [7], the increase in tHcy after N 2 O anaesthesia was very marked, while in the third, randomised and controlled study, the tHcy increase was about 70% [9].…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The finding that tHcy levels did not change or slightly increased in patients who were randomly allocated to receive anaesthesia with N 2 O is compatible with the known inhibitory effect of N 2 O on cobalamin which acts as a cofactor of methionine synthase, the key enzyme in the remethylation pathway of homocysteine to methionine [1, 2]. Three previous studies have shown that tHcy increases after surgery [7–9]. In two of these, which were uncontrolled [8] or non‐randomised [7], the increase in tHcy after N 2 O anaesthesia was very marked, while in the third, randomised and controlled study, the tHcy increase was about 70% [9].…”
Section: Discussionmentioning
confidence: 61%
“…Three previous studies have shown that tHcy increases after surgery [7–9]. In two of these, which were uncontrolled [8] or non‐randomised [7], the increase in tHcy after N 2 O anaesthesia was very marked, while in the third, randomised and controlled study, the tHcy increase was about 70% [9]. The greater effect of N 2 O on tHcy in those studies compared to ours may be explained by differences in the patient populations studied and, most likely, in the duration of anaesthesia, because the inhibitory effect of N 2 O on cobalamin is time‐dependent [4, 19], being biologically relevant only for exposure times exceeding 2 h [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Nitrous oxide alters cobalamine metabolism within 1 h of administration, resulting in increased Hcy concentrations that can remain elevated for longer than 1 week. 21 Fenofibrate, bezafibrate, and colestipol in combination with niacin result in hyperhomocysteinemia by yet to be defined mechanisms. 22,23 Tobacco and caffeinated coffee are also associated with increased Hcy concentrations.…”
Section: Etiology Of Hyperhomocysteinemiamentioning
confidence: 99%
“…Agents interfering with vitamin B,, metabolism. Plasma H(e) increases within 90 min of exposure to nitrous oxide [64]. The amount of increase is related to the duration of anaesthesia and persists for at least 1 week.…”
Section: Hornocyst(e)inaemia and Pharmacological Agents Not Includingmentioning
confidence: 99%